Processing Tofu Liquid Waste into Liquid Organic Fertilizer through Fermentation Process in Penggalang Village, Cilacap Regency - Aini, Tisfi Khilmi Nurul; Priyanto, Meisya Nisrina; Anto, Eko Dwi; Mulya, Devita Krisna Jati; Salsabila, Maulin Shofi; Resmi, Mutiara Nada; Ardita, Vinu; Pamuningtyas, Astrilina; Annajah, Kamaluddin; Ridlo, Akhmad; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
The process of making tofu produces large amounts of liquid waste, especially at the boiling and filtering stages of soybeans. This waste has a high organic matter content so that if disposed of directly into the environment it can cause water pollution, unpleasant odors, and health problems. Based on these problems, community service activities in Penggalang Village were carried out with the aim of processing tofu liquid waste into liquid organic fertilizer through a fermentation process. The methods used included counseling the community on the negative impacts of tofu liquid waste and its potential utilization, followed by technical training on making liquid organic fertilizer. In the training stage, tofu liquid waste is mixed with additional ingredients such as EM4 or tape yeast, molasses or brown sugar, and rice washing water. The mixture is stirred until evenly distributed, then fermented for 7-14 days in a closed container. After the fermentation process is complete, the resulting liquid organic fertilizer is ready to be used for plant fertilization by the community. This activity involved 11 students of Universitas Muhammadiyah Purwokerto and went well thanks to the active participation of the community, especially the tofu factory owners. This program is not only able to reduce the negative impact of tofu liquid waste on the environment, but also improve the skills and independence of residents in managing waste, while providing a cheap, environmentally friendly, and beneficial alternative to organic fertilizer for local agriculture.